Designing Comprehensive Public Health Surveillance for Enteric Fever in Endemic Countries: Importance of Including Different Healthcare Facilities. (27th July 2018) - Saha, Senjuti; Islam, Maksuda; Saha, Shampa; Uddin, Mohammad Jamal; Rahman, Hafizur; Das, Rajib Chandra; Hasan, Md; Amin, Md Ruhul; Hanif, Mohammed; Shahidullah, Mohammad; Hussain, Manzoor; Saha, Samir K
Abstract: Background: Designing comprehensive surveillance to generate credible burden estimates of enteric fever in an endemic country can be challenging because care-seeking behavior is complex and surveillance in different healthcare facilities may lead to documentation of different epidemiological characteristics. Methods: We conducted retrospective surveillance in 3 healthcare facilities to identify culture-confirmed enteric fever cases in Dhaka, Bangladesh, from January 2012 through December 2016. The study settings included (1) hospital in-patient department (IPD), (2) hospital out-patient department (OPD), and (3) private consultation center OPD. We analyzed the cases to understand their distribution, age ranges, and antibiotic susceptibility patterns across the settings. Results: Of the 1837 culture-confirmed enteric fever cases, 59% (1079 of 1837) were OPD cases. Children with enteric fever hospitalized in the IPDs were younger than children seeking care at the hospital OPD (median age: 45 vs 60 months) or private OPD (median age: 45 vs 72 months). Multidrug resistance rates were slightly higher in hospital IPD cases than in private OPD cases (26% vs 24%). Conclusions: In each facility, we identified different epidemiological characteristics, and lack of consideration of any of these may result in misinterpretation of disease burden, identification of different age groups, and/or antibiotic susceptibility patterns.